"A FESTIVAL OF BRIGANDS": IN SEARCH OF DEMOCRACY AND POLITICAL LEGITIMACY IN MALI (The Strategic Review for Southern Africa, 2020)
Mali's coup d'état in March 2012 and the subsequent occupation of northern Mali by Islamist and separatist rebels took many observers by surprise. How could an erstwhile model of peaceful democratic transition collapse so swiftly? Why did so few ordinary Malians stand up in defence of their 20-year-old democracy? Combining accounts from Malian and foreign journalists with observations made in Bamako leading up to and during the dramatic events of early 2012, this article assesses the failures of Mali's pre-coup political system. A combination of the tenuous rule of law, weak state institutions, and perceptions of systemic corruption deeply eroded Malians' faith in their democracy. The junta that ousted Mali's elected president in March 2012, despite its international isolation, skillfully manipulated public frustrations with the government as well as local symbols and discourses pertaining to heroic leaders to gain support and legitimacy at home. The crisis in Mali was preceded by certain warning signs, some of which might be applied to gauge the health of democratic transitions elsewhere in Africa.